Information Literacy Skills of Library and Information Science Study Program Students at Muhammadiyah University of Sinjai in Completing Assignments Using the Big Six Literacy Method - Amalia, Nur; Syamsuddin, Syamsuddin; Harianto, Harianto (Universitas Negeri Padang, 2024)
This study aims to analyze the information literacy skills of students in the Library and Information Science Program at Universitas Muhammadiyah Sinjai in completing academic assignments using the Big Six method. This research employs a qualitative method with a descriptive approach. The data used in this study were obtained through interviews with Library and Information Science students at Universitas Muhammadiyah Sinjai. The results of the study indicate that students generally possess fairly good information literacy skills. They are able to go through the main stages in the information management process, such as defining problems, searching for and accessing information, organizing data, and evaluating results. However, there are several aspects that still need improvement, including validating information sources, maintaining consistency in recording important information, and addressing access barriers to resources.